Oral Presentation No. 03 Growth differentiation factor-15 and bleeding complication risk in patients with coronary artery disease, receiving combined antithrombotic therapy. (21st October 2022) - Krivosheeva, E; Komarov, A; Dobrovolsky, A; Titaeva, E; Balakhonova, T; Panchenko, E
Abstract: Introduction: Recent studies are aimed to find laboratory predictors of bleeding complications in patients receiving various regimens of antithrombotic therapy. One of these biomarkers is GDF-15. Purpose: To study the significance of GDF-15 in relation to the development of bleeding outcomes in CAD patients with multifocal atherosclerosis, receiving combined antithrombotic therapy. Methods: The data was obtained from the prospective registry REGATA-1 (NCT04347200). 122 patients (90 males), median age 69 [IQR 64; 76] yrs) with CAD and peripheral atherosclerosis of at least one vascular territory (≥ 50%), were enrolled. Half of the patients (47.5%) with sinus rhythm received acetylsalicylic acid in combination with rivaroxaban 2.5 mg bid. Other patients (52.5%) with concomitant atrial fibrillation received direct oral anticoagulants in combination with antiplatelet therapy after elective PCI. Median follow-up was 10 months [IQR 7.0;12.0]. The safety end point was BARC 2–5 bleedings. Plasma samples for GDF-15 identification were taken at the inclusion and analyzed using ELISA. Results: Frequency of BARC 2–5 bleedings was 14%. Median GDF-15 level was 1248.5 pg/ml [947.8; 1791.0]. According to the quartile analysis, GDF-15 values in the top three quartiles of the distribution (cut-off value > 948 pg/ml) were associated with higher frequency of bleeding events: 3.1% versus 17.8%, P = 0.0411. Bleeding-free survival in groups, formed depending on the level of GDF-15 (948 > and ≤ 948 pg/ml), was 96.7% vs. 82.2%, respectively, Log-Rank P = 0.0408. Conclusions: Increase in GDF-15 level (> 948 pg/ml) is associated with the development of BARC 2-5 bleedings in CAD patients with multifocal atherosclerosis, receiving combined antithrombotic therapy.